Revisiting the five problems of public sector organisations and reputation management—the perspective of higher education practitioners and ex-academics - Päivikki Kuoppakangas; Kati Suomi; Jari Stenvall; Elias Pekkola; Jussi Kivistö; Tomi Kallio (Springer, 2022)
The extant literature has identified five problems related to public sector organisations and their reputation management: politics, consistency, charisma, uniqueness and excellence. This study examines whether and how the problems of reputation management occur in public higher education by collecting qualitative data from 40 interviews. The study sheds light on the perceptions of a group that has been largely neglected in previous studies: namely, doctorates who have exited academia, or ex-academics. In addition to ex-academics, interviewees also included their employers and university leadership. The analysis follows a thematic qualitative approach with an abductive logic. The study provides empirical evidence of the content of the problems in higher education and discusses recent related transformations in higher education. The findings show that, in terms of reputation management, the most challenging matters appear to be knowledge transfer and the applicability of research to practice. These challenges are cross-cutting and apparent from different angles across all five problems of reputation management. This study contributes to the academic literature on reputation management in the public sector by applying prior conceptual categorizations and employing a comprehensive set of empirical data with a fresh perspective. The study presents implications for higher education policy makers and managers and emphasises the need for university management to minimise the duality between different types of workers, as this duality threatens university reputations in general and consistency in particular.